Vegetation Composition of Savanna Ecosystem as a Habitat For The Komodo Dragon (Varanus komodoensis) on Padar and Komodo Islands, Flores East Nusa Tenggara Indonesia - S. Sutomo (Universitas Gadjah Mada, 2020)
Tropical savanna and dry forest in Indonesia are an important type of ecosystem that supports various endemic wildlife of Indonesia including savannas at Padar and Komodo Islands which is home to the Komodo (Varanus komodoensis). The Komodo dragon is considered as “Vulnerable” by the International Union for Conservation of Nature. Studies with regards to the Komodo dragons’ habitats are scarce, considering that these types of habitats are significant to support Komodo’s existence, but yet are also very prone to conversion and disturbances. This paper elaborates the results of ecological study on the tropical savanna forest in Komodo National Park as habitat for the Komodo dragon. Vegetation sampling was conducted using nested plots 20 x 20 m, 10 x 10 m, 5 x 5 m and 2 x 2 m spread across the sampling sites. Data was analysed using PRIMER software which includes cluster analysis, analysis of similarity (ANOSIM) and similarity percentage (SIMPER). As many as 17 plant species which belongs to 11 families were identified in the sampling sites. These consist of six trees habitus, six shrubs, four grasses and one palm. Asteraceae, Fabaceae and Poaceae were the plant families which has high number of species. The result of cluster analysis shows that the similarity level of the two groups (Komodo and Padar) based on the results of cluster analysis is 60%. This result infers that there are similarities in terms of species composition in savanna on Komodo and Padar Island, however, each savanna still has its own species characteristics. This is confirmed by the ANOSIM test. The ANOSIM test results show the Global R value of 0.6.With the looming challenges from invasive alien plant species (IAPS), the Komodo Island’s savanna has double threats to overcome. Hence conservation of the remaining savanna ecosystem is important